2005
DOI: 10.1007/s10047-004-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the internal environment in total artificial heart (TAH) recipients during long-term pumping

Abstract: Sixty-six long-term experiments were performed on animals (65 calves, 1 goat) after implantation with a total artificial heart (TAH). Animal survival ranged from 30 to 314 days using TAH devices ranging from the TNS-BRNO-II to the TNS-BRNO-VIIII. In these experiments some basic problems were studied which need to be overcome to achieve the optimal physiological status of the animal, the optimal maintenance of the internal environment, and the long-term survival of TAH recipients. The problem areas studied were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In all our experiments, we have consistently kept the pulsatile regimen as our microcirculatory study showed the physiological prevalence of the pulsatile pumping (22). Recently, we have confirmed in close cooperation with the Department of Biomedical Engineering,Tokyo University that this concept might be more realistic than the pulseless pumping (23,24).…”
mentioning
confidence: 78%
“…In all our experiments, we have consistently kept the pulsatile regimen as our microcirculatory study showed the physiological prevalence of the pulsatile pumping (22). Recently, we have confirmed in close cooperation with the Department of Biomedical Engineering,Tokyo University that this concept might be more realistic than the pulseless pumping (23,24).…”
mentioning
confidence: 78%